?-CAROTENE PRODUCTION FROM OIL PALM EMPTY FRUIT BUNCHES (OPEFB) WHICH WERE GROWN BY NEUROSPORA SP. - Shavero Purba, Mien
In the food and beverage industry, the addition of food coloring has become a common thing to increase attractiveness. However, Indonesia still relies on imports to meet around 60-70% of the need for food coloring, one of which is ?-carotene. ?- carotene is a red-orange natural pigment contained in crude palm oil. Naturally, ?- carotene can also be produced by Neurospora sp. which can grow in oil palm empty fruit bunches (OPEFB). The levels of ?-carotene that can be obtained vary depending on the factors that influence the production of ?-carotene by Neurospora sp. This study aims to determine the effect of the Neurospora sp. starter mass grown in OPEFB and the effect of adding nutrients in OPEFB to the concentration of ?-carotene extracted from OPEFB that is overgrown by Neurospora sp. ?-carotene production using Neurospora sp. in OPEFB done with variations in the Neurospora sp. starter mass (0, 1, 2 grams) and nutrient concentrations in the form of urea (0, 5, 10 mM) and MgSO4 (0, 5, 10 mM). The ?-carotene produced was then extracted with n-hexane at 70?C for 3 hours and analyzed using a UV-Vis spectrophotometer at 449 nm. The conclusion obtained from this study is the addition of starter mass in OPEFB can increase the concentration of ?-carotene in the extract, but it is not significant. Addition of MgSO4 and urea separately with a concentration of 5 mM and 10 mM in the OPEFB inoculum gave a significant effect on the concentration of ?- carotene in the extract compared to variations without the addition of MgSO4 or urea. However, the ?-carotene concentrations of the two variations of 5 mM and 10 mM did not differ significantly from each other, while the addition of the combination of urea and MgSO4 had a significant effect on the concentration of ?-carotene in the extract and had interactions with each other. The maximum ?-carotene acquisition in this study can be achieved by adding urea 10 mM and 10 mM MgSO4 with the acquisition of 0.045 mg ?-carotene/g OPEFB and by aproximating doing the fermentation using fresh OPEFB, the acquisition of ?-carotene can reach 0.511 mg ?-carotene/g OPEFB.